THE PROSPECT OF ISLAMIC MICROFINANCE INSTITUTION IN INDONESIA - Kholis, Nur (Episteme: Jurnal Pengembangan Ilmu Keislaman, 2012)
The Islamic microfinance institution is well known as Baitul Mal Wattamwil (BMT).The purpose of establishing the BMT is to help micro and medium entrepreneurs to be able to access financing to develop their business. The BMT stimulates and supports people to establish and develop it only by having a modal of knowledge, for example philosophy, management of BMT and having short orientation that leads to the emerge of problem in the BMT. Consequently, many problems occur, such as mismatch of fund allocation, fraud of depositor fund, moral hazard that lead to the collapse of the BMT. Regarding to those problem, it needs to identify problems and challenge faced by the BMT from the aspects of supervision, operational management, resources and other related instruments. Moreover, it is also necessary to design solution of the problem as well as to arrange recommendation to the authoritative people to solve the problem.Institusi keuangan mikro Islam di Indonesia dikenal sebagai Baitul Mal Wattamwil (BMT). Tujuan dibentuknya BMT adalah untuk membantu pengusaha mikro, kecil dan menengah agar bisa mengakses pembiayaan dalam rangka mengembangkan usaha. BMT mendorong banyak pihak untuk mendirikan dan mengembangkan BMT dengan hanya berbekal ilmu baik tentang filosofi, pengelolaan BMT dan berorientasi jangka pendek yang berdampak pada BMT yang bermasalah. Akibatnya banyak persoalan muncul seperti alokasi dana yang tidak tepat, kecurangan pengelola, moral hazard dan bahkan berujung dengan kolapnya BMT tersebut. Dari hal tersebut perlu mengidentifikasi persoalan dan tantangan yang dihadapi BMT baik dari sisi regulasi, supervisi, manajemen operasional, sumber daya, maupun instrumen-instrumen yang terkait. Barulah kemudian mendesain tawaran solutif untuk menyelesaikan persoalan dan menaklukkan tantangan, sekaligus menyusun rekomendasi pada pihak-pihak berotoritas untuk memitigasi dan menyelesaikan persoalan.